2011
DOI: 10.1111/j.1365-2109.2011.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation effect(s) of organic acids and/or lipid to plant protein-based diets on juvenile yellowtail, Seriola quinqueradiata Temminck et Schlegel 1845, growth and, nitrogen and phosphorus excretion

Abstract: A feeding experiment was conducted to investigate the e¡ect of organic acids and/or lipid supplementation on growth, utilization and environmental loading of nitrogen (N) and phosphorus (P) in juvenile yellowtail fed ¢shmeal (FM) and plant protein (PP) diets. Six diets as FM (FM-based), FM1P (FM with inorganic P), FM1L (FM with lipid), PP1CA (PP with citric acid), PP1L1CA (PP with lipid and citric acid) and PP1L1FA (PP with formic acid) were formulated.Yellowtails were fed each of the diets in duplicate groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…It also lowers the gut pH which favors the digestive enzymes working hence increasing nutrients absorption. Similar to our study, improved DM content was also observed in yellowtail (Sarker et al, 2012) and red sea bream (Hossain et al, 2007) in response to dietary acidification through different organic acids.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It also lowers the gut pH which favors the digestive enzymes working hence increasing nutrients absorption. Similar to our study, improved DM content was also observed in yellowtail (Sarker et al, 2012) and red sea bream (Hossain et al, 2007) in response to dietary acidification through different organic acids.…”
Section: Discussionsupporting
confidence: 91%
“…Difference in the diet composition and formulation and fish species and fish rearing conditions might have contributed to these contradictory results. Sarker et al (2012) described that CA may positively influence the proximate composition of moisture, lipid and ash in yellowtail positively.…”
Section: Discussionmentioning
confidence: 99%
“…Brenes et al (2003) found that the inclusion of CA depressed the growth performance of broiler chicks but caused an increase in mineral utilization. Previous experiments conducted with Seriola quinqueradiata and Pagrus major have demonstrated that supplementation with organic acids can serve to reduce the fishmeal component in diets for these species and to avoid the use of inorganic phosphates by enhancing the bioavailability of P and other minerals present in dietary alternative protein ingredients (Sarker et al, 2007;Sarker et al, 2012). Our results are in agreement with the results of a study by Pandey and Satoh (2008) in which different organic acids were evaluated in low-fishmeal diets for rainbow trout.…”
Section: Discussionsupporting
confidence: 90%
“…If this effect can be reproduced in diets formulated with low-P plant alternative ingredients, the addition of citric acid would be a useful approach for reducing inorganic P supplementation and the total P in the excreta, thereby limiting the environmental impacts of fish culture effluents. More recent investigations have shown that organic acid supplementation in diets for marine and freshwater fish can increase the P bioavailability of plant protein ingredients, making it possible to reduce the fishmeal component and avoiding the use of supplemental phosphates (Sarker et al, 2007;Pandey and Satoh, 2008;Sarker et al, 2012;Khajepour and Hosseini, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports on the benefit of organic acids in aquatic animals, including red hybrid tilapia [18], yellowtail [19] and Pacific white shrimp [20]. The organic acids and salts used are formic acid/calcium formate, acetic acid/ sodium acetate, propionic acid/ calcium propionate or butyric acid/ sodium butyrate that are in the free form and they can enhance the growth performance and health status of fish.…”
Section: Discussionmentioning
confidence: 99%